PELATIHAN MOTIVASI PADA SISWA SMK TUNAS MUDA BERKARYA BATU AJI BATAM - Tiurniari Purba (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2022)
The progress of a nation can be seen from the growth and development of the education of its people. This shows that education is the basic key of a country. Education is often likened to a symbol of the strength, authority and greatness of a nation anywhere in the world. Education is essentially a human need, no exception. This has been explained in paragraph 4 in the Preamble to the 1945 Constitution that the purpose of the state is to participate in the intellectual life of the nation. Then in Article 31 of the 1945 Constitution it is also stated that every citizen has the right to education and teaching. Concrete efforts that need to be encouraged are developing and improving Human Resources (HR) through educational development. Tri Dharma of Higher Education as a guide for lecturers in carrying out their duties as an educator. One of the contents of the tri dharma of higher education is community service as a vehicle for socialization between lecturers and the community. Therefore, as a form of lecturer service to the community, PKM is carried out at SMK Tunas Muda Berkarya Batu Aji Batam. The form of this PKM is to hold training with the title